CTLA-4 Blockade Resistance after Relatlimab and Nivolumab - Menzies, Alexander M; Pires da Silva, Ines; Trojaniello, Claudia; Vieu, Elisabeth; Amaria, Rodabe N; Zimmer, Lisa; Lo, Serigne N; Burton, Elizabeth M; Tawbi, Hussein A; Schadendorf, Dirk; Grob, Jean J; Ascierto, Paolo A; et al. (The New England journal of medicine, 2022)
Data were pooled from 36 patients who received the anti–CTLA-4 antibody ipilimumab after metastatic melanoma progression during therapy with nivolumab (anti–PD-1) plus relatlimab (anti–LAG-3) to assess whether immunotherapies that target distinct checkpoints have different mechanisms of action. The findings suggest that cross-resistance emerges when tumors progress with immune checkpoint inhibitors.